KOMODIFIKASI DAN MAKNA SIMBOLIK MOTIF TENUN MUNA SEBAGAI BENTUK KEARIFAN LOKAL MASYARAKAT KABUPATEN MUNA - Wa Ode Lusianai; Aryuni Salpiana Jabar; Ikrima Nurfikria; Sitti Hairani Idrus (Journal Publicuho, 2019)
Local weaving is the identity and wealth inherent in some area. Muna Regency, Southeast Sulawesi, is known to have regional weaving with diverse and interesting qualities and motifs. There are many previous Muna weaving motifs such as dhalima, samasili, panino toghe, bhotu, bhia-bhia, ledha, finda ngkonini, mango-manggopa, lante-lante, kambheano bhanggai, tibha-tibha, kaholeno ghunteli, kambhampu, bharalu, kasokasopa. To balance the development of the fashion industry, through the creative ideas of weavers, Muna's weaving motifs undergo commodification called a series of motifs. The visual of the first Muna weaving and Muna weaving produced by commodification and also the symbolic meaning of Muna woven motifs as a result of commodification became a problem in this study. Located in Masalili Village, Muna Regency, researchers conducted observations and direct interviews with research informants. By using the qualitative descriptive analysis of Milles and Huberman's interactive model, it was found that from the visuals of Muna's weaving motifs, after experiencing commodification, the latest motifs have been produced. Whether it's a combination of samasili and butterfly motifs, samasili and kites and other types of motifs. The development of the commodification motif has its own symbolic meaning. It describes the regional identity, cultural preservation, openness with progress, diversity, and describes the value of local wisdom in integrating outside cultural elements into the development of the Muna weaving motif.     Keywords: commodification; symbolic meaning; local wisdom; Muna weaving.